The Validity of Student Worksheets Based on Problem-Based Learning in Human Blood Type System Sub Materials to Train Critical Thinking Skill for Senior High School Students - Maghfiroh, Sabila; Ducha, Nur; Purnama, Erlix Rakhmad (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
Critical thinking skill is one of the competencies students must master to be able to confront the challenges of 21st-century education. The government seeks to compile the 2013 curriculum with learner-centered learning that is relevant to daily life. Learning that is relevant in daily life, one of which is the learning of Biology in the sub materials of Human Blood Type System. One alternative that can be used to facilitate students in developing their critical thinking skills is by providing them teaching materials forms students worksheets based on Problem Based Learning (PBL). This study aimed to produce PBL-based Students Worksheets to train students’ critical thinking skills in the sub material of Human Blood type System based on the feasibility of presentation, content, and language. This study used the 4D model there were define, design, develop, disseminate. The stages carried out only up until the development stage. The validity of Students Worksheets was determined based on the results of the validation by three validators using the validation sheet instrument. Aspects of validity rated include aspects of presentation, content, language, worksheets characteristics to train critical thinking skills, and PBL-oriented worksheets characteristics. The results showed that the PBL-based worksheets in this study obtained a validity score of 3.95 with a very valid category. Based on the results of the validity, it can be concluded that the developed PBL-based worksheets in this study can be used in the teaching and learning process to train students' critical thinking skills. Keywords: Validation, PBL-based worksheet, human blood type, critical thinking skills.